2017
DOI: 10.12688/f1000research.8461.3
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary results on the control of Aedes spp. in a remote Guatemalan community vulnerable to dengue, chikungunya and Zika virus: community participation and use of low-cost ecological ovillantas for mosquito control

Abstract: Objective: To study the effectiveness of an integrated intervention of health worker training, a low-cost ecological mosquito ovitrap, and community engagement on Aedes spp. mosquito control over 10 months in 2015 in an urban remote community in Guatemala at risk of dengue, chikungunya and Zika virus transmission. Methods: We implemented a three-component integrated intervention consisting of: web-based training of local health personnel in vector control, cluster-randomized assignment of an ecological modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Some types of programmes have been implemented to control the mosquito borne diseases Zika, Dengue and Chikungunya through vector management. [48-50, 52, 53, 57, 59, 62-69] Some studies focused on awareness healthcare campaigns about the sexual transmission of Zika virus and contraception programmes. [8, 32-37, 54, 75] Others discussed a family support approach and provided information about family support services.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some types of programmes have been implemented to control the mosquito borne diseases Zika, Dengue and Chikungunya through vector management. [48-50, 52, 53, 57, 59, 62-69] Some studies focused on awareness healthcare campaigns about the sexual transmission of Zika virus and contraception programmes. [8, 32-37, 54, 75] Others discussed a family support approach and provided information about family support services.…”
Section: Resultsmentioning
confidence: 99%
“…Among the studies, which reported mosquito vector control initiatives, several publications reported community engagement projects of mosquito vector control and described the active involvement of communities into the planning, developing and implementation process of an initiative. [48, 50, 57, 59, 62, 64-66] . A community-based participatory approach was provided among a community in the Amazon basin of Peru and at the same time among a community in Thailand.…”
Section: Resultsmentioning
confidence: 99%
“…Because "egg-laying females were most attracted to sites containing other immature Aedes, rather than to sites containing the most food" [9], home traps could become especially attractive to gravid females, and therefore be disproportionally important in reducing the mosquito population. Alternatively, attractants can be added to encourage mosquitoes to preferentially use lethal ovitraps that can be managed or left to biodegrade rather than inaccessible natural PBRPs [32][33][34]. The Mosquito Drain posits that it is not necessary to eliminate all breeding sites to cause the population to crash, which would not be practicable anyway, but that by (i) removing manageable breeding sites (e.g.…”
Section: Box 2 Mosquito Drainmentioning
confidence: 99%
“…World Health Assembly, due to the high toxicity, low selectivity of chemical pesticides and the increase resistance of the species, recommended to use new methods of vector control, such as biological (16). In this sense, vector control is no longer based only on applying chemical agents, for the above environmental reasons; a study with ovillantas in 2017 showed that the decrease in Aedes spp can be due to the implementation of a simple ovillanta (with no chemicals) and the active participation of the community in the affected area (17). In this study, according to preliminary calculations, the systematic elimination of larvae and eggs in the application area, caused a reduction of up to 77% of Aedes spp.…”
Section: Introductionmentioning
confidence: 99%